The characteristics of bacteremia among patients with acute febrile illness requiring hospitalization in Indonesia. - Pratiwi Soedarmono; Aly Diana; Patricia Tauran; Dewi Lokida; Abu Tholib Aman; Bachti Alisjahbana; Dona Arlinda; Emiliana Tjitra; Herman Kosasih; Ketut Tuti Parwati Merati; Mansyur Arif; Muhammad Hussein Gasem; et al. (PLoS ONE, 2022)
Blood culturing remains the "gold standard" for bloodstream infection (BSI) diagnosis, but the method is inaccessible to many developing countries due to high costs and insufficient resources. To better understand the utility of blood cultures among patients in Indonesia, a country where blood cultures are not routinely performed, we evaluated data from a previous cohort study that included blood cultures for all participants. An acute febrile illness study was conducted from July 2013 to June 2016 at eight major hospitals in seven provincial capitals in Indonesia. All participants presented with a fever, and two-sided aerobic blood cultures were performed within 48 hours of hospital admission. Positive cultures were further assessed for antimicrobial resistance (AMR) patterns. Specimens from participants with negative culture results were screened by advanced molecular and serological methods for evidence of causal pathogens. Blood cultures were performed for 1,459 of 1,464 participants, and the 70.6% (1,030) participants that were negative by dengue NS1 antigen test were included in further analysis. Bacteremia was observed in 8.9% (92) participants, with the most frequent pathogens being Salmonella enterica serovar Typhi (41) and Paratyphi A (10), Escherichia coli (14), and Staphylococcus aureus (10). Two S. Paratyphi A cases had evidence of AMR, and several E. coli cases were multidrug resistant (42.9%, 6/14) or monoresistant (14.3%, 2/14). Culture contamination was observed in 3.6% (37) cases. Molecular and serological assays identified etiological agents in participants having negative cultures, with 23.1% to 90% of cases being missed by blood cultures. Blood cultures are a valuable diagnostic tool for hospitalized patients presenting with fever. In Indonesia, pre-screening patients for the most common viral infections, such as dengue, influenza, and chikungunya viruses, would maximize the benefit to the patient while also conserving resources. Blood cultures should also be supplemented with advanced laboratory tests when available.